Pycamilonum effects on quaternidin effectiveness and safety in acute occlusion-reperfusion heart damage - A. A. Kotlyarov; E. D. Fomicheva; I. Ya. Moiseeva; V. V. Babin (Российский кардиологический журнал)
.